EVALUASI SISTEM PENYANGGAAN PADA TUNNEL 4 BERDASARKAN METODE RMR-SYSTEM DI PT. AICJ, SAWAHLUNTO - Alvi Zichri; Raimon Kopa (Journals Mining Engineering : Bina Tambang, 2021)
Abstract. Excavation of underground rock masses results in changes in the balance of rock conditions such as rock collapse and changes in tunnel dimensions due to shifting of stress distribution. Good geotechnical analysis is desirable to provide proper treatment of the excavated rock.This research was conducted to determine rock mass class, rock mass classification using the RMR method, determine the strength of the rock in tunnel 4 of PT AICJ Sawahlunto, obtain Stand Up Time and span buffer values as references for installing mine pit buffers, obtain appropriate support system recommendations based on the results grounsuppport RMR (Bieniawski 1989) on tunnel 4, Obtaining the condition of the wooden supports used in tunnel 4 of PT AICJ at this time.From the measurement of several parameters of the RMR method, it is obtained that tunnel 4 for coal is in class III (fair rock) with a coal RMR value of 53, and silstone is in class II (good rock) with a value of 61. Based on the stress value received on the cap and side post, namely 502.85 Kg/cm2 and 74.898 Kg/cm2 with the value of the wood clearance stress of 623.75 Kg/cm2 . So that the FK value on the cap and side post tunnel 4 are 1.24 and 8,32. So the tunnel cap 4 is recommended to use wooden supports with a diameter from 20 cm to 21 cm so that the FK value has increased to 1,60 and is declared safe (> 1.5).Keywords: Underground, Rock Mass Ratting, Stress, Safety Factor, Wooden Support.